Colombia : Agricultural and Rural Competitiveness - World Bank (Washington, DC, 2013)
The purpose of this study is to assess agriculture's competitiveness in Colombia. During the past 12 years, Colombia's agricultural sector has performed poorly, resulting in the continuation of extensive rural poverty. Improving the sector's competitiveness is the only sure and lasting way to improve its growth performance and reduce poverty. Thus, the main objectives of this study are to assess: (a) the sector's current and potential competitiveness, (b) the factors that determine or inhibit its competitiveness, (c) the extent to which the campesino economy is competitive and could become more so, and (d) the role of policies in determining the sector's competitiveness. The study outlines strategic options that would strengthen the sector's competitiveness, with emphasis on development of transition measures to ease the path to adoption of new orientations. The work has been organized around three main themes: (a) the competitiveness of products and product chains, (b) underlying factors that influence competitiveness, and (c) policy orientations that influence competitiveness.